Pengaruh Layanan Beranda Tenas Effendy Terhadap Pemanfaatan Koleksi Konten Lokal di Dispusip Kota Pekanbaru: Penelitian - Salwa Arina; Nurizzati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of the Beranda Tenas Effendy Service on the utilization of local content collections at the Library and Archives Office of Pekanbaru City. The research employed a quantitative method with a descriptive approach. The population consisted of 507 visitors, with the sample determined using the Slovin formula, resulting in 84 respondents selected through purposive sampling. The research instrument was a questionnaire using a 4-point Likert scale. Validity testing was conducted using the Pearson Product Moment correlation, while reliability testing employed Cronbach’s Alpha. Classical assumption tests included normality, heteroscedasticity, and linearity tests. Data analysis utilized simple linear regression. The results indicate that all questionnaire items were valid and reliable, the data were normally distributed, there was no heteroscedasticity, and the relationship between variables was linear. The regression results showed that the Beranda Tenas Effendy Service had a significant effect on the utilization of local content collections, with a significance value of 0.000 < 0.05, a correlation coefficient of 0.608 (strong relationship), and a coefficient of determination of 37%. The regression equation obtained was Y = 18.983 + 0.853X, meaning that each one-unit increase in the Beranda Tenas Effendy service could increase the utilization of local content collections by 0.853 units.